Evaluation of Dietary Intake, Leisure-Time Physical Activity, and Metabolic Profile in Women with Mutation in the LMNA Gene. (19th May 2017) - Monteiro, Luciana; Foss-Freitas, Maria Cristina; Navarro, Anderson; Pereira, Francisco; Coeli, Fernanda; Carneseca, Estela; Júnior, Renan Montenegro; Foss, Milton
ABSTRACT: Introduction : Familial partial lipodystrophy (FPL) is a rare genetic disorder characterized by selective lack of subcutaneous fat, which is associated with insulin-resistant diabetes. The Dunnigan variety (FPLD2) is caused by several missense mutations in the lamin A/C ( LMNA ) gene, most of which are typically located in exon 8 at the codon position 482. Objective : The aim of this study was to assess and compare the dietary intake, leisure-time physical activity (LTPA), and biochemical measurements (glucose, A1C, and plasma lipids) in women with FPLD2 and without (control group, CG) and to examine the associations between dietary intake and biochemical measurements (BM). Methods : LTPA was measured with a questionnaire and metabolic equivalent (MET) hours per week (hours/week) were calculated. Dietary intake by the 3-day recall method and clinical laboratory parameters were collected. Results : Characteristics of women with FPLD2: 35.8 ± 13.9 years, fat mass = 10 ± 2.3 kg and fat free mass = 41.4 ± 4.5 kg ( p < 0.05). Women with FPLD2 showed a smaller intake of energy (kcal), lipids, and carbohydrates and a large intake of protein ( p < 0.01) compared to CG. Comparing the 2 groups in terms of LTPA, 78% of women with FPLD2 performed insufficient physical activity. In addition, they had a higher levels of glucose, A1C, and triglycerides (TG) and lower levels of high-density lipoprotein (HDL). There was no correlation between dietary intake and biochemical measurements. Conclusions : Women with FPLD2 have a lower intake of energy (kcal), lipids, and carbohydrates and greater changes in biochemical measurements. Because this is a rare disease, future studies are needed with encouragement of the practice of physical activity and of healthy eating habits, preventing the onset of diseases.